Pengaruh Kemiskinan dan Pengangguran Terhadap Pertumbuhan Ekonomi di Sumatera Utara - Alda Eliya Nasution (Asosiasi Dosen Akuntansi Indonesia, 2025)
Poverty and unemployment are major challenges for economic development in developing countries, including Indonesia. This study aims to analyze the impact of unemployment and poverty rates on economic growth in North Sumatra Province. Through secondary data analysis from the Central Statistics Agency (BPS), the results of the study indicate a significant negative relationship between unemployment and poverty on economic growth, which is reflected in the decline in the province's Gross Domestic Product (GDP).